2021
DOI: 10.1002/cnr2.1397
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors in Wilms' tumor and Neuroblastoma: What now?

Abstract: Background: Therapeutic activation of tumor-infiltrating lymphocytes using monoclonal antibodies targeting PD1 or PD-L1 (immune checkpoint inhibitors-ICIs) has revolutionized treatment of specific solid tumors in adult cancer patients, and much hope has been placed on a similar effect in relapsed or refractory solid pediatric tumors. Recent clinical trials have disappointingly shown an almost nonexistent response rate, while case reports have demonstrated that some pediatric patients do achieve durable respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We further postulate that appropriate reactivation and enhancement of immune function may be beneficial for pediatric WT therapy. Furthermore, no significant treatment efficacy was observed with the use of an immune checkpoint inhibitor targeting PD-L1 for pediatric tumors, including WT patients [ 47 ]. We found that NK cells were enriched higher in high-risk patients with WT.…”
Section: Discussionmentioning
confidence: 99%
“…We further postulate that appropriate reactivation and enhancement of immune function may be beneficial for pediatric WT therapy. Furthermore, no significant treatment efficacy was observed with the use of an immune checkpoint inhibitor targeting PD-L1 for pediatric tumors, including WT patients [ 47 ]. We found that NK cells were enriched higher in high-risk patients with WT.…”
Section: Discussionmentioning
confidence: 99%
“… 15 The occurrence of such an unwanted event (xGvHD) in “melanoma PDX models” is quite expectable given that the melanoma is classified among the highly immunogenic tumors with high TIL density, 17 and a proper candidate for immune checkpoint inhibitor treatments. 18 , 19 However, for WT, which is not listed among lymphocyte‐predominant solid tumors, 3 , 20 the incidence of xGvHD in PDX models has been unexpected and not been reported elsewhere. Not only in xenografting of the solid tumors, but also in hematologic malignancies, the presence of cotransplanted lymphocytes can 1 mask the engraftment of the original tumor, 2 develop posttransplant lymphoproliferative disorder, or 3 cause xGvHD.…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis showed that non-MYCN amplified NB patients have a high neo-antigen burden. This group was, however, found to have less PD-1 and PD-L1 expression compared to adult tumors but a degree of CD8+ tumor infiltrating lymphocytes (TIL) that was comparable to adult malignancies [ 51 ]. Preclinical NB murine models have demonstrated modest response to PD-1/PD-L1 and CTLA-4 blockade [ 52 , 53 ].…”
Section: Checkpoint Inhibitor Use In Pediatric Oncologymentioning
confidence: 99%
“…This group also performed a nested case-control study and established that favorable histology patients with more than 60% expression for PD-L1 were at a high risk of treatment failure of initial therapy [ 59 ]. In a landscape paper by Valind et al, a higher neo-antigen burden was detected in TP53 -mutated WT, and this subgroup of WT patients may potentially benefit from ICI therapy [ 51 ].…”
Section: Checkpoint Inhibitor Use In Pediatric Oncologymentioning
confidence: 99%